Burundi : 2008 Article IV Consultation and Request for Three-Year Arrangement Under the Poverty Reduction and Growth Facility; Staff Report; Public Information Notice and Press Release on the Executive Board Discussion; and Statement by the Executive Director for Burundi. (IMF Staff Country Reports; Country Report ;, 2008)
This 2008 Article IV Consultation highlights that Burundi is emerging slowly from more than a decade of civil conflict. GDP per capita is about USD 139, and only 18 percent of the population is food secure. Economic growth slowed down while inflation increased in 2007. External developments were dominated by a decline in exports and a sharp rise in grants. Executive Directors have commended the authorities for the progress they have made in implementing Burundi's first Poverty Reduction and Growth Facility-supported program in a difficult post-conflict environment.